Molecular Characterization of Pestiviruses in Fetal Bovine Sera Originating From Argentina: Evidence of Circulation of HoBi-Like Viruses - Pecora, Andrea; Perez Aguirreburualde, Maria Sol; Ridpath, Julia Francis; Dus Santos, María José (Frontiers in Veterinary Science, 2019)
Serological evidence suggests that HoBi-like viruses, an emerging species within the Pestivirus genus of the Flavivirus family, are in circulation in Argentina. While HoBi-like viruses were first isolated from Brazilian origin fetal bovine, no survey of Argentine origin fetal bovine serum has been conducted. Therefore, 124 local batches of non-irradiated fetal bovine serum (FBS) originating in Argentina were surveyed for the presence of pestiviruses using RT-PCR. Amplicons from pestivirus positive samples were genotyped. Four samples were positive for HoBi virus-specific RT-PCR, while the BVDV-positive samples (n=45) were classified as BVDV-1b (82.2%), BVDV-1a (13.3%) and BVDV-2 (4.5%). Virus isolation and serological profile assessment were performed for the four HoBi-positive FBS lots. These results confirm the circulation of HoBi-like virus in the Argentinean territory, highlighting the need to review the diagnostic techniques currently used in the clinical cases suspected of BVDV and in contamination control protocols for adventitious agents in cells and biotechnological products.